2022
DOI: 10.1037/cou0000565
|View full text |Cite
|
Sign up to set email alerts
|

Career decision-making in unemployed Portuguese adults: Test of the social cognitive model of career self-management.

Abstract: Most research applications of the social cognitive model of career self-management (CSM; Lent & Brown, 2013) to career exploration and decision-making have involved U.S. college students. To extend research on the model, we tested its fit to the data in a sample of 345 unemployed adult workers in Portugal. Participants completed measures of career decision self-efficacy, outcome expectations, social support, conscientiousness, neuroticism, exploration goals, decisional stress, and career choice certainty. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…The CSM model has different applications for different career behaviors such as career exploration and CDM (Ireland & Lent, 2018;Lent et al, 2016Lent et al, , 2017. Based on the CSM and through the results of an empirical study of 345 unemployed adult workers, in Portugal, Lent et al (2022) showed that the CSM model can provide explanatory utility relative to initial and subsequent CDM and across national boundaries. Stremersch et al (2021) incorporated the job search quality of college students into the CSM model, and the results confirmed the validity of this integration.…”
Section: Theory and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The CSM model has different applications for different career behaviors such as career exploration and CDM (Ireland & Lent, 2018;Lent et al, 2016Lent et al, , 2017. Based on the CSM and through the results of an empirical study of 345 unemployed adult workers, in Portugal, Lent et al (2022) showed that the CSM model can provide explanatory utility relative to initial and subsequent CDM and across national boundaries. Stremersch et al (2021) incorporated the job search quality of college students into the CSM model, and the results confirmed the validity of this integration.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…The manifestation of goals in professional behavior, which can be called ''career goals,'' plays an important role in career management. However, it is often implicit and is usually understood as a person's intention to engage in a certain activity or to achieve a specific level of performance (Lent et al, 2022). Intention is a prerequisite for relevant behavior, and the stronger the intention, the greater the likelihood of converting the intention into action (Ajzen, 1991).…”
Section: Research Hypothesismentioning
confidence: 99%
“…According to a meta-analysis study, individuals with positive beliefs related to career development and positive expectations about the outcomes of their efforts have increased active participation in decisions related to career development and experience reduced career indecisiveness (Choi et al, 2012). Similarly, research showed that self-efficacy and outcome expectations positively related to decisional outcomes (e.g., decisional stress, choice certainty) (Lent et al, 2022), exploratory goals and career decidedness (Lent et al, 2016(Lent et al, , 2019.…”
Section: Cognitive-person Factorsmentioning
confidence: 99%
“…Additionally, personality traits in the CSM model are assumed to affect career adjustment by activating the individual's affective coping tendencies and making behavioral performance easier (Lent & Brown, 2013). Studies found positive correlations between a variety of personality traits with CDMSE (Ojeda et al, 2012), career goals (Hirschi, 2010), choice certainty (Lent et al, 2022), and career decidedness (Lounsbury et al, 2005; Penn & Lent, 2019). Among these five-factor personality traits, individuals with high conscientiousness levels may approach the career research process with more self-confidence and optimism due to higher probability of determining career goals, and being organized and persistent (Lent et al, 2016).…”
Section: Contextual and Personality Factorsmentioning
confidence: 99%
“…Studying this particular age group is of special importance because aspirations formed in early adulthood may remain comparably stable across the life course (Low et al, 2005). Hence, periods of unemployment in these formative years may shape career goals and expectations (Lent & Brown, 2013;Lent et al, 2022). As early-career unemployment spells have become more common in recent decades, studying the heterogenous consequences of youth unemployment becomes increasingly relevant (O'Reilly et al, 2015;Ralston et al, 2021).…”
Section: Introductionmentioning
confidence: 99%